Plasmapheresis in severe methemoglobinemia following occupational exposure. Issue 3 (June 2017) - Shatila, Wassim; Verma, Amanda; Adam, Soheir
Abstract: Ferrous iron can be converted to ferric iron by oxidative stress which results in the formation of methemoglobin. Consequently, the oxygen dissociation curve is shifted to the left, which leads to tissue hypoxia and ultimately may cause death. Acquired methemoglobinemia can be due to a host of offending agents and chemicals including nitrites, local anesthetics, aniline and antimalarial drugs. There are several approaches to the management of methemoglobinemia. The first step is to stop the offending agent and initiate supportive measures. Methylene blue can be used successfully provided the patient has no evidence of glucose 6 phosphate deficiency. Hyperbaric oxygen and intravenous ascorbic acid are other treatment options. We present a case of unusually severe methemoglobinemia (82% methemoglobin) secondary to occupational exposure that failed to respond to several lines of management including methylene blue, red cell exchange, intravenous ascorbic acid, and hyperbaric oxygen. However, the patient responded swiftly to plasmapheresis started upon suspicion of concomitant thrombotic thrombocytopenic purpura, and he subsequently recovered completely. Thus, plasmapheresis may have a role in severe methemoglonbinemia unresponsive to standard treatment options.